Analysis of Fault Locations Using the Impedance Method on the GIS 150 kV Transmission Line Karang Pilang Surabaya - Reza Sarwo Widagdo; Budiono, Gatut; Aris Heri Andriawan; Puji Slamet; Putra, Roy Wibatsu (Jurnal Poli-Teknologi, 2024)
Transmission lines often experience difficulties in determining the location of interference, due to the length of the transmission line. This interference can be secured by using relays, one of which is a distance relay, this tool secures the zone 1, zone 2 and zone 3 areas on the transmission line. Apart from relays, there is also a tool to determine the fault distance, namely a fault locator. These two tools are examples of protection on transmission lines. The method used in this research uses the impedance method to determine the distance the fault occurs and the settings on the distance relay. This technique is often used in electric power systems and is very effective for transmission lines, such as those in Karang Pilang, because of its ability to detect disturbances in transmission lines and equipment. Based on the analysis results, calculating the fault distance using the impedance method shows that the calculated value is very close to the distance measured by the fault finder. Specifically when a short circuit occurs, the impedance method calculates a distance of 14.35 km, while the fault locator measures it at 14.59 km with a margin of error of 1.5%.